2018
DOI: 10.1016/j.bbrc.2018.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal epithelial cell-specific Raptor is essential for high fat diet-induced weight gain in mice

Abstract: Mammalian target of rapamycin complex 1 (mTORC1) is a major regulator of cell growth and proliferation through fuel sensing. Systemic inhibition of mTOR as well as manipulation of its downstream products prevent diet-induced obesity. The purpose of this study was to determine the consequences of intestine-targeted mTORC1 inhibition. To attenuate intestinal mTORC1 activity, Villin-CreER mice were crossed with Raptorflox/flox mice, creating an intestinal-specific Raptor null line (i-Raptor −/−). Mice were fed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Calorie intake impacts the gene associated with cg26633077, RPTOR , as shown in the stabilization of the MTOR-RPTOR association by nutrient deprivation, leading to inhibition of MTOR activity [ 56 ]. Despite the inhibition of the anabolic regulator MTOR, one study found that RPTOR null mice gained less weight, most likely due to reduced food intake in a high-fat diet, when compared to wild type mice [ 57 ]. It is worth noting that there was very high heterogeneity observed for cg26633077.…”
Section: Discussionmentioning
confidence: 99%
“…Calorie intake impacts the gene associated with cg26633077, RPTOR , as shown in the stabilization of the MTOR-RPTOR association by nutrient deprivation, leading to inhibition of MTOR activity [ 56 ]. Despite the inhibition of the anabolic regulator MTOR, one study found that RPTOR null mice gained less weight, most likely due to reduced food intake in a high-fat diet, when compared to wild type mice [ 57 ]. It is worth noting that there was very high heterogeneity observed for cg26633077.…”
Section: Discussionmentioning
confidence: 99%